Brassinosteroid preharvest treatments as a useful tool to increase crop yield and red colour in blood orange fruits - Garrido-Auñón, Fernando; Puente-Moreno, Jenifer; García-Pastor, María E.; Zapata, Pedro J.; Martínez-Romero, Domingo; Serrano, María; Valero, Daniel (Frontiers in Plant Science, 2025)
IntroductionBlood oranges are highly appreciated by consumers due to their attractive peel, red-colour juice, and their antioxidant and other health-beneficial properties. However, increased temperatures due to climate change compromise anthocyanin biosynthesis, depreciating their market value. Brassinosteroids (BRs) are plant hormones with important effects in plant adaptation to environmental stresses.Materials and methodsThe present experiment aimed to evaluate the effects of tree foliar treatments with different 24-epibrassinolide (24-BL) concentrations (0.01, 0.1, and 1 μM) on crop yield and fruit quality properties of the “Sanguinelli” blood oranges, with special emphasis on anthocyanin content in the peel and juice.ResultsThe results of 2-year experiments (2021–2022 and 2022–2023, carried out in Alicante, Spain) showed that 24-BL treatments improved total crop yield. Fruit quality properties, such as firmness, total soluble solids, and titratable acidity, were also enhanced, as well as red colour in the flavedo and juice, due to enhanced total and individual anthocyanin concentrations.DiscussionThe greatest improvements were recorded at the 0.1-μM 24-BL treatment, in which the enhanced peel colour led to a 41% increase in the yield of commercial fruits compared to control trees, which could have an important beneficial impact on growers’ profit. In addition, the consumer acceptance of 24-BL could increase since the red colour in blood oranges is the most important parameter valued by consumers. With the enhancement of their total anthocyanin and phenolic contents, their health-beneficial effects are also increased.